Is criminality in-born? An Islamic perspective - Abd Rashid, Adnan (Leena and Luna International, Chikusei-shi, Japan, 2016)
According to the teachings of Islam human beings are born into this world in the clean and precious in the sight of Allah. In the Qur'an Allah describes man was created with the best creation and certified by Allah preferred them from other creatures. They are given intellect and freedom to choose something good or bad in their life and they are responsible for their actions . However there is an opinion from the West claim that human misbehavior and crime is because hereditary. For their crimes and vices inherited from the past and their descendants rather than external influences or the environment. This paper discusses whether the criminals it is descended from the past in the view of Islam . Is it true that Western allegations that it inherited criminals ? Arguments conclusions of this paper explains that the Western view of the criminals was the inheritance is not true at all.